UPLC-QTOF-ESI-MS/MS-Based Comparative Study of Phytochemicals in Sapindus mukorossi - Neil Patrick Uy; Hak-Dong Lee; Jajung Ku; Kyung Choi; Sanghyun Lee (Horticulturae, 2025)
This study examined the phytochemical compositions of ten Sapindus mukorossi samples from two regions in Korea: Suwon and Daegu. The Folin–Ciocalteu method was used to calculate the total polyphenol content (TPC). Among all extracts tested, leaf samples from Suwon and Daegu (SLE and DLE) exhibited the highest TPC at 2.70 and 2.90 mg tannic acid equivalent/g extract. Similarly, a modified aluminum chloride colorimetric test was used to determine the total flavonoid content (TFC). Similar results were obtained, with SLE and DLE having TFC values of 40.71 and 41.07 mg quercetin equivalent/g extract, respectively. Liquid chromatography with tandem mass spectrometry was used to detect 13 compounds, whereas high-performance liquid chromatography was used to quantify the prominent compounds: rutin, nicotiflorin, and narcissin. Among these, rutin was the most abundant, especially in SLE and DLE (54.37 and 70.21 mg/g, respectively). Furthermore, rutin significantly contributed to the total content of these samples at 78.31 and 85.44 mg/g, respectively. There were significant variations in the distribution of these compounds across different parts of the plant. These findings highlight the importance of S. mukorossi as a source of natural bioactive chemicals and pave the way for further research into its potential applications in healthcare products.